Women, Law and John Stuart Mill. Issue 2 (3rd March 2016) - Ward, Ian; McGlynn, Clare
Abstract : John Stuart Mill's intellectual reputation is unarguable; his liberal credentials seemingly impeccable. Moreover there seems to be a Mill for everyone; liberal, radical, feminist. The precise nature of the feminist Mill has however remained a matter of considerable debate. The purpose of this article is less to engage this speculation, but rather to invite closer consideration of what Mill actually said and wrote about women and the law in nineteenth-century England. For Mill, the law was both an instrument of women's subjection and a prospective means of liberation.